2022
DOI: 10.3389/fonc.2022.972550
|View full text |Cite
|
Sign up to set email alerts
|

The expression, clinical relevance, and prognostic significance of HJURP in cholangiocarcinoma

Abstract: BackgroundCholangiocarcinoma (CCA) is the malignancy originating from the biliary epithelium, including intrahepatic (iCCA), perihilar (pCCA), and distal (dCCA) CCA. The prognosis of CCA is very poor, and the biomarkers of different CCA subsets should be investigated separately. Holliday junction recognition protein (HJURP) is a key component of the pre-nucleosomal complex, which is responsible for normal mitosis. The ectopic expression of HJURP has been reported in several cancers, but not CCA.Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The role of HJURP in biliary tract neoplasia was investigated by Yang et al who reported increased HJURP expression in cholangiocarcinoma (CCA) tissue samples compared to non-tumorous ones. Additionally, HJURP overexpression was associated with lower OS in cases of intrahepatic and perihilar CCA but not in patients with distal CCA [52]. Thus, the study highlights the potential role of HJURP as a tumor-promoting factor (Figure 2) and a marker of worse prognosis (Figure 3) in CCAs.…”
Section: Biliary Tractmentioning
confidence: 71%
“…The role of HJURP in biliary tract neoplasia was investigated by Yang et al who reported increased HJURP expression in cholangiocarcinoma (CCA) tissue samples compared to non-tumorous ones. Additionally, HJURP overexpression was associated with lower OS in cases of intrahepatic and perihilar CCA but not in patients with distal CCA [52]. Thus, the study highlights the potential role of HJURP as a tumor-promoting factor (Figure 2) and a marker of worse prognosis (Figure 3) in CCAs.…”
Section: Biliary Tractmentioning
confidence: 71%
“…The ectopic expression of HJURP and its prognostic significance in various subtypes of CCA, including intrahepatic (iCCA), perihilar (pCCA), and distal (dCCA) CCA, were investigated [13]. HJURP is highly expressed in all subtypes of CCA and serves as an independent prognostic biomarker in iCCA and pCCA, but not dCCA.…”
Section: Cholangiocarcinoma (Cca)mentioning
confidence: 99%
“…The HJURP activation requirement for cancer cell immortality was initially identified in 2007 [9,10]. Furthermore, overexpression of HJURP has been observed in various tumor tissues and is associated with poor prognosis, thus making HJURP a potential prognostic cancer biomarker [11][12][13][14]. Given these findings, HJURP could be a key target for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, HJURP activates EMT through upregulation of Sphingosine kinase 1 (SPHK1), causing upregulation of vimentin and N-cadherin and downregulation of E-cadherin to promote tumor cell migration, invasion, and metastasis in vivo ( Chen T. et al, 2019 ) ( Figure 4 ). In a recent study employing bioinformatics analysis and immunohistochemistry, Yang et al reported that HJURP was highly expressed in cholangiocarcinoma (CCA) samples ( Yang et al, 2022 ). High expression of HJURP was associated with low overall survival in intrahepatic CCA and perihilar CCA, but not in distal CCA ( Yang et al, 2022 ).…”
Section: Roles Of Hjurp In Tumorsmentioning
confidence: 99%
“…In a recent study employing bioinformatics analysis and immunohistochemistry, Yang et al reported that HJURP was highly expressed in cholangiocarcinoma (CCA) samples ( Yang et al, 2022 ). High expression of HJURP was associated with low overall survival in intrahepatic CCA and perihilar CCA, but not in distal CCA ( Yang et al, 2022 ). Luo et al reported that high HJURP expression in HCC was associated with tumor-infiltrating immune cells, immune checkpoints, and immunosuppression, verified by gene sequencing analysis ( Luo et al, 2022 ).…”
Section: Roles Of Hjurp In Tumorsmentioning
confidence: 99%